Characterization of rheological and physicochemical properties of Alaska walleye pollock (Gadus chalcogrammus) roe - Anvari, Mohammad (J Food Sci Technol, 2018)
Alaska walleye pollock (Gadus chalcogrammus) roe is a commercial product of the Alaska pollock fishery. Accordingly, the objective of this study was to determine functional properties of pollock roe through rheological and physicochemical analyses. Pollock roe rheological properties were determined by flow sweep and frequency sweep measurements. Zeta potential of the roe was measured at different pHs (2–12) and roe protein concentration of 0.05% (w/v). Protein solubility was determined by adjusting pH of the freeze-dried pollock roe powder between 2 and 12. Emulsion stability of the roe was determined by measuring creaming index at different oil:water ratios ranging from 5:95 to 65:35 (w/w). The obtained results showed that emulsifying activities of the pollock roe were high (2.93 ± 0.03 ml oil/g roe). Higher oil phase volume resulted in more stable emulsions. The highest charge densities were at pH 2 and 12, where the maximum protein solubility occurred. The DSC thermogram for the pollock roe exhibited a single endothermic peak at 82.89 °C in average, indicated thermal denaturation of the fish roe proteins. Rheological behaviors of the roe were determined as a function of temperature (5 and 25 °C). Viscosity profile showed shear thinning behavior in both samples. However, the pseudoplasticity degree (N) and viscosity values increased by decreasing temperature. The mechanical spectra derived from strain sweep and frequency sweep measurements indicated viscoelastic behavior in all of the samples. However, higher dynamic moduli values at lower temperatures suggested more molecular connectivity and network formation, which was likely caused by protein–protein interactions.